2014
DOI: 10.4103/0970-9185.137273
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intraarticular dexamethasone for postoperative analgesia after arthroscopic knee surgery

Abstract: Background and Aims:In an attempt to improve the recovery and early rehabilitation after arthroscopic knee surgery, various medications have been administered via intra-articular route to prolong the duration and improve the quality of postoperative analgesia. Among the potentially effective substances, steroids like dexamethasone could be of particular interest.Materials and Methods:Fifty patients undergoing elective knee arthroscopy were randomly assigned to one of the following groups containing 25 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…Corticosteroids may be administered through the intra-articular route to decrease the intensity and duration of pain [19]. Scholten et al [20] confirmed that fluoroscopically guided corticosteroid injections, based on arthrographic contrast patterns, into the superior portion of SIJ were effective in de- for LBP, this study did not find any statistically significant difference in the mean BMI between the discharged and transferred groups.…”
Section: Discussionmentioning
confidence: 51%
“…Corticosteroids may be administered through the intra-articular route to decrease the intensity and duration of pain [19]. Scholten et al [20] confirmed that fluoroscopically guided corticosteroid injections, based on arthrographic contrast patterns, into the superior portion of SIJ were effective in de- for LBP, this study did not find any statistically significant difference in the mean BMI between the discharged and transferred groups.…”
Section: Discussionmentioning
confidence: 51%
“…Dexamethasone is a potent and highly selective glucocorticoid with minimal mineralocorticoid effects. It inhibits nociceptive impulse transmission along myelinated C-fibers, and when combined with local anesthetics, it increases the duration of regional blocks (28,29). Intraarticular ropivacaine has only been shown to be effective when it is administered with other drugs, not when used alone (15) ; therefore, dexamethasone was used in this study to increase analgesic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Levobupivacaine is S-enantiomer of bupivacaine and has a longer effect compared to bupivacaine. There is no study regarding levobupivacaine toxicity in IA administration and data on its IA use is limited ( 12 - 16 ). In a study by Kazak Bengisun et al ( 16 ), IA levobupivacaine and bupivacaine were compared with saline (control); both local anesthetics decreased pain scores at rest and after movement and consumption of postoperative tramadol compared saline.…”
Section: Discussionmentioning
confidence: 99%